2019
DOI: 10.1177/1747493019851284
|View full text |Cite
|
Sign up to set email alerts
|

A national economic and clinical model for ischemic stroke care development in Saudi Arabia: A call for change

Abstract: Background: Stroke is a significant burden in Saudi Arabia and the Saudi Ministry of Health's stroke committee has identified an urgent need to improve care.Aim: The purpose of this study was to undertake a health-economic analysis to quantify the impact of developing stroke care in the country.Methods: An economic model was developed to assess the costs and clinical outcomes associated with an ischemic stroke care development program compared with current stroke care. Based on Saudi epidemiological data, coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“… 18 , 19 The majority of the studies evaluated costs from the health-care system perspective, which refers to a variety of bodies, including hospitals (n = 8) 17 , 20 , 23 , 24 , 26 , 27 , 29 , 30 or public payers (n = 1), 28 with one additionally considering the societal perspective. 30 Societal (n = 2) 22 , 25 and patient (n = 1) 21 perspectives were also adopted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 18 , 19 The majority of the studies evaluated costs from the health-care system perspective, which refers to a variety of bodies, including hospitals (n = 8) 17 , 20 , 23 , 24 , 26 , 27 , 29 , 30 or public payers (n = 1), 28 with one additionally considering the societal perspective. 30 Societal (n = 2) 22 , 25 and patient (n = 1) 21 perspectives were also adopted.…”
Section: Resultsmentioning
confidence: 99%
“…The costing year was explicitly reported in 10 studies; the remaining studies reported the year for the conversion rate. 18 , 19 , 24 , 25 A variety of currency data was reported: Five studies used both the local currency and international dollars, 18 , 19 , 23 , 29 , 30 five studies used international dollars, 17 , 21 , 25–27 and the remaining four studies used the local currency. 20 , 22 , 24 , 28 …”
Section: Resultsmentioning
confidence: 99%
“…Despite the convincing evidence for thrombolysis in the management of acute stroke, particularly during the first 4.5 hours, Saudi Arabia struggles to move from traditional stroke care, with approximately 95% of patients being cared for at nonspecialized stroke hospitals and not receive any reperfusion therapy. 9 In Saudi Arabia, the estimated proportion of eligible stroke patients who received IV t-PA is still <1%, although it is currently standard care and has been approved since 1996. 9 One of the major challenges is the shortage of neurologists.…”
Section: Discussionmentioning
confidence: 99%
“…9 In Saudi Arabia, the estimated proportion of eligible stroke patients who received IV t-PA is still <1%, although it is currently standard care and has been approved since 1996. 9 One of the major challenges is the shortage of neurologists. A previous study conducted in Saudi Arabia in 2011 reported that there were solely 83 practicing neurologists working in Saudi Arabia at that time, almost half of whom practiced in the capital city of Riyadh.…”
Section: Discussionmentioning
confidence: 99%
“…5 Furthermore, stroke care is still suboptimal as compared to developed countries, 6 and there is a lack of robust organizational processes of care and inadequate allocation of resources. 6,7 This would in turn cause significant consequences in the affected patients.…”
mentioning
confidence: 99%